Nerve Transfers for an Upper Brachial Plexus Injury: A Case Report - Ferry Senjaya (Indonesian Journal of Physical Medicine & Rehabilitation, 2014)
Objective: To demonstrate multiple nerve transfers as primary surgical management for an upperplexus injury.Methods: A 6-year-old boy who suffered a preganglionic upper brachial plexus injury following a motor vehicle accident, exhibited complete biceps, deltoids, suprapinatus, and infraspinatus palsies.Multiple nerve transfers, which consist of spinal accessory nerves to suprascapular nerve transfer, median and ulnar motor fascicles to biceps and brachialis motor branches transfers, and long head oftriceps motor branch to axillary nerve transfer were performed 6 months after injury.Results: 13 months post multiple nerve transfer, the patient has regained M4+/5 elbow flexion, M4/5 external rotation, and M4/5 shoulder abduction.Conclusion: Nerve transfer is a viable option for upper plexus palsy management. With a sound surgical technique and good case selection, the results can be very rewarding. This case showedquite robust re-innervation with significant functional recovery at a one-year follow-up following multiple nerve transfers.Keywords: Brachial Plexus Injury, Upper Plexus Injury, Nerve Root Avulsion, Nerve Transfers, Functional Recovery.